Quality Control Evaluation of Tapyadi Loha Using Physicochemical and HPTLC Parameters - Dr. Suchita Ware; Prof. (Dr.) Vaishali Deshpande; Dr. Lekshmi C. S (The Bioscan, 2026)
Sickle Cell Anaemia (SCA) is a chronic inherited haemoglobin disorder that is characterized by haemolytic anaemia, oxidative damage, inflammation, and involvement of various organs. In Ayurvedic practice, such symptoms can be attributed to Pāṇḍu Roga, which is treated with Loha-based herbo-mineral formulations.